Therukoothu: Living Folk Theatre and the Spatial Culture of Tamil Villages - Parameswari, A (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2026)
Therukoothu, the traditional street theatre of Tamil Nadu, is a major folk performance deeply rooted in village tradition, social organization, and collective cultural memory. Unlike classical theatre traditions that depend on enclosed stages and passive spectatorship, Therukoothu is performed in open public spaces such as village streets, temple courtyards and festival grounds, where performers and audiences share a common cultural and social space. This paper examines stage, space and audience interaction in Therukoothu as cultural traits rather than merely technical or performative elements. It argues that the absence of a fixed stage, the ritual use of everyday village spaces, and the active participation of the audience express key Tamil folk values such as social equality and communal living. The paper further interprets Therukoothu as a form of spatial democracy, where no rigid boundary exists between performer and spectator. The 360-degree performance arena brings together the sacred, mythological and social worlds. By analysing performances conducted in village streets, temple grounds and shared public spaces, this study demonstrates that the “street” in Therukoothu is not merely a venue but a ritual and cultural landscape. Through oral tradition, shared space and participatory performance, Therukoothu continues to sustain living cultural traditions of Tamil folk society.